The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/s0100-83582014000200001
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic action of parthenium and its rhizospheric soil on maize as influenced by growing conditions

Abstract: -Biosynthesis and subsequent release of allelochemicals by a plant into the environment is supposed to be influenced by its growing conditions. To ascertain what will be the allelopathic action of plant parts and rhizospheric soils of parthenium (Parthenium hysterophorus) growing at various farm locations with varied growing conditions, germination and seedling growth of maize hybrid (DK 6142) were assayed by sowing its seeds in petri plates lined with filter paper and pots filled with soil. Minimum germinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
4
13
0
4
Order By: Relevance
“…2.8 0.9 NS In a column, value with different letters show significant difference (P≤0.05), EP= emergence percentage, GI= emergence index, MGT= mean emergence time, T50 = time to 50% emergence. Our results are in line with those of Safdar et al (2014) who investigated that rhizospheric soil of P. hysterophorus significantly reduced the germination of maize. In contrast to our results, Hussain et al (2011) concluded that soil collected underneath L. camara had no allelopathic effects on the test species.…”
Section: Soil Bioassay Studiessupporting
confidence: 93%
See 1 more Smart Citation
“…2.8 0.9 NS In a column, value with different letters show significant difference (P≤0.05), EP= emergence percentage, GI= emergence index, MGT= mean emergence time, T50 = time to 50% emergence. Our results are in line with those of Safdar et al (2014) who investigated that rhizospheric soil of P. hysterophorus significantly reduced the germination of maize. In contrast to our results, Hussain et al (2011) concluded that soil collected underneath L. camara had no allelopathic effects on the test species.…”
Section: Soil Bioassay Studiessupporting
confidence: 93%
“…All weeds except L. camara showed significant inhibitory effect on shoot and root lengths, seedling length, and seedling biomass of crops. Our results are similar to the findings of Tanveer et al (2014) and Safdar et al (2014) that showed that leaf extract of A. aspera and P. hysterophorus significantly reduced the seedling length of maize. However our findings are contradictory to the observations of Hossain and Alam (2010), Sharma et al (2005) and Ahmed et al (2007) who reported significant inhibitory effect of L. camara on the growth of agricultural crops.…”
Section: Aqueous Extract Bioassay Studiessupporting
confidence: 92%
“…Parthenin has been reported as a germination and radicle growth inhibitor in a variety of dicot and monocot plants. The allelochemicals released from plants may inhibit shoot/root growth and nutrient uptake, or they may attack a naturally occurring symbiotic relationship thereby destroying the plants' usable source of nutrients (Conn, 1980;Khan et al, 2005;Hassan, et al, 2008;Safdar et al, 2014). There have been previous reports of the inhibitory effects of P. hysterophorus, an invasive alien weed, on germination of many crops (Meirse and Singh, 1987;Maharjan et al, 2007;Acharya and Rahman, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…These residues affected the growth of radish and mustard by releasing phenolics rather than decreasing the available nutrient status in the soil (Batish et al, 2005a,b). Many studies about allelopathic interference of parthenium pertain to the fresh parts or freshly collected Germination and seedling growth inhibition Srivastava et al, 1985;Singh et al, 1992;Rashid et al, 2008;Pandey et al, 2011 Rice Leaf Complete failure of seed germination Singh, 1991;Maharjan et al, 2007;Pandey et al, 2011 Johnson grass Leaf Reduced activities of amylase, invertase, dehydrogenase, nitrate reductase, peroxidase, polyphenol oxidase in germinating seeds, increase in ATPase activity, decrease in level of reducing and non-reducing sugars Pawar and Chavan, 2007 Wheat Leaf, inflorescence, stem, root Reduction in germination, root/shoot length, their dry weights, leaf area, spikelet number, and seed weight Rajan, 1973;Rao et al, 1977;Srivastava et al, 1985;Patil and Hedge, 1988;Singh, 1991;Agarwal and Anand, 1992;Oudhia, 2001;Singh et al, 2005a;Dongre and Singh, 2007;Maharjan et al, 2007;Bhawana et al, 2009;Sarika et al, 2010, Pandey et al, 2011 Leaf and root Germination and seedling growth inhibition Maharjan et al, 2007;Rashid et al, 2008;Khan et al, 2011;Pandey et al, 2011, Safdar et al, 2014 Pulses Chickpea Leaf, stem, root, inflorescence…”
Section: Allelopathic Effect Of Partheniummentioning
confidence: 99%